Highly Dispersed Mo2C Nanodots in Carbon Nanocages Derived from Mo‐Based Xerogel: Efficient Electrocatalysts for Hydrogen Evolution. Issue 11 (17th September 2021) - Du, Qianqian; Zhao, Ruihua; Guo, Tianyu; Liu, Lu; Chen, Xiaojun; Zhang, Jie; Du, Jianping; Li, Jinping; Mai, Liqiang; Asefa, Tewodros
Abstract: The production of hydrogen via electrochemical water splitting has the potential to enable the utilization of hydrogen‐powered fuel cells on a large scale. However, to realize this technology, inexpensive, noble metal‐free electrocatalysts possessing high performances for the hydrogen evolution reaction (HER) are needed. Mo2 C nanoparticles recently receive much attention as alternative noble metal‐free electrocatalysts because their electronic structures are akin to that of Pt. However, the synthesis of Mo2 C at nanoscale with high catalytic activity for HER remains a great challenge. Moreover, although efforts have been made to prevent their aggregation, the particles coalesce during high temperature carbonization, which is typically used to produce such transition metal carbides. Here, the synthesis of Mo2 C nanodots that are well‐dispersed within 3D cage‐like carbon microparticles using rationally designed Mo‐based xerogels, which are prepared via the sol–gel process as precursors, is reported. During their pyrolysis, the xerogels maintain their structures while the Mo species in them transform into well‐dispersed Mo2 C nanodots in situ. The as‐synthesized Mo2 C nanodots exhibit excellent electrocatalytic activity for HER, in both alkaline and acidic media, while remaining largely stable. The work also demonstrates a promising synthetic route and procedure to other well‐dispersed yet stable nanocatalysts. Abstract : 3D nanocarbon cages‐supported molybdenum carbide (Mo2 C) nanodots are synthesized by pyrolysis of rationally designed Mo‐based xerogels. The cage‐like nanocarbon confines the Mo2 C nanodots and prevents them from sintering during pyrolysis (or their synthesis). The as‐synthesized 3D Mo2 C/C material exhibits high activity and stability for the hydrogen evolution reaction (HER).